Doing things differently: Exploring attachment patterns and parental intentions in families where a child has a diagnosis of autism. (October 2020) - Bond, Nicholas; Dallos, Rudi; McKenzie, Rebecca
The article examines the experience of parenting a child with a diagnosis of autism with a focus on scripts and intentions in relation to the parents' own childhood experiences of being parented. Five parents participated in a multiple case study design involving in-depth interviews, Adult Attachment Interviews and a parenting intentions scaling task. The findings revealed that all of the parents had experienced significant adverse events in their own childhoods, including trauma and losses. They also expressed intentions to offer parenting that was 'corrective' in terms of providing a better emotional environment for their children. Their corrective attempts and also intentions to repeat positive aspects of being parented were moderated by unconscious aspects of their early childhood experiences and also by the autistic features of their children. The interplay between early embodied experiences, theories of autism, parenting experiences and intentions is discussed along with clinical implications.